Malt sprout, an underused beer by-product with promising potential for the growth and dehydration of lactobacilli strains - Cejas, Luján (2017)
Malt sprout (MS), a by-product of the malt industry obtained by removing rootlets and sprouts from the seed of germinated barley (Hordeum vulgare L.), was used as culture, dehydration and storage medium of three strains of lactobacilli: Lactobacillus salivarius CM-CIDCA 1231B and CM-CIDCA 1232Y and Lactobacillus plantarum CIDCA 83114. The three strains were grown in MS and MS supplemented with 20% w/v fructo-oligosaccharides (MS FOS). Bacterial growth was determined by registering the decrease of pH and by plate counting. Comparable results with those of microorganisms grown in MRS (controls) were observed in terms of lag times, DpH and acidification rates. Furthermore, during fermentation, a significant increase of DP6 (FOS with degree of polymerization 6) was observed at expenses of inulin and DP7, probably indicating their hydrolysis. A concomitant decrease of DP3, sucrose and monosaccharides was also observed, as result of their bacterial consumption during growth. The presence of FOS in the fermented media protected microorganisms during freeze-drying and storage, as no decrease of culturability was observed after 60 days at 4 C ([108 CFU/mL). Using MS appears as an innovative strategy for the production of lactobacilli at large scale, supporting their use for the elaboration of functional foods containing prebiotics and probiotics.